2022
DOI: 10.52533/johs.2022.2606
|View full text |Cite
|
Sign up to set email alerts
|

Etiology, Epidemiology, Assessment and Prognosis of Globe Rupture

Ahmed Alnahdi,
Ali Artam Alajmi,
Khaled Alsaadi
et al.

Abstract: Ocular trauma, which is a globe injury, is one of the most prevalent eye diseases, leading to hospitalization and severe eye deficits. The term globe rupture is used to describe a wide range of globe injuries. Globe rupture is defined as globe injury caused by the blunt object or due to an impact with inside-out mechanism. Globe injuries are expected to cause 3.5 eye injuries per 100,000 people worldwide, leading to about 203,000 new cases each year. Globe rupture is one of the most serious globe injuries resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
(23 reference statements)
0
1
0
Order By: Relevance
“… 7 It has been suggested that the rate of ocular trauma in men is 6 times higher than in women, and these traumas in young children and adolescents are usually penetrating caused by accidents, sports-related incidents, automobiles, or other causes. 8 Limited studies have investigated the prevalence of ocular trauma in Iran. Accordingly, the majority of cases with trauma-related ocular injuries were men, and the main causes included accidents, industrial jobs, chemical agents, foreign bodies, and burns.…”
Section: Introductionmentioning
confidence: 99%
“… 7 It has been suggested that the rate of ocular trauma in men is 6 times higher than in women, and these traumas in young children and adolescents are usually penetrating caused by accidents, sports-related incidents, automobiles, or other causes. 8 Limited studies have investigated the prevalence of ocular trauma in Iran. Accordingly, the majority of cases with trauma-related ocular injuries were men, and the main causes included accidents, industrial jobs, chemical agents, foreign bodies, and burns.…”
Section: Introductionmentioning
confidence: 99%